Power quality improvement and analysis of interconnected bus system with PMU using VSM-STATCOM - Preeti Nitin Kabra; Sudha Rani Donepudi (Institute of Advanced Engineering and Science, 2022)
The traditional static synchronous compensator (STATCOM) present in the power grid to compensate instability problem will not be not able to maintain stability of the system due to fluctuations in point of common coupling (PCC) voltage and frequency variation that may result in poor synchronization of the grid. The solution for this is the improvement in conventional STATCOM to virtual synchronous machine–static synchronous compensator (VSM-STATCOM). In this paper an interconnected IEEE-14 bus system is considered for analysis with VSM-STATCOM for improvement in voltage profile on weakest bus of the system. In order to find the weakest bus, load flow analysis is carried out on the bus system using Newton Rapson method. A VSM-STATCOM is connected at that weakest bus in synchronization to the grid injecting reactive power. For the analysis a fault is introduced on any of the line and voltage profile of the weakest bus is observed with and without VSM-STATCOM. The VSM-STATCOM is also compared to a conventional control STATCOM which has no inertia module. A comparative analysis is carrier out with parameters of voltage magnitude and frequency of the weak bus taken into consideration. The magnitude and frequency parameters of conventional STATCOM and VSM-STATCOM are measured using phasor measurement units. The model is designed using MATLAB Simulink power systems library block sets with graphical user interface (GUI) environment.